Respostas

2014-04-20T00:00:08-03:00
É só vc iguala a função a 0:
 a) F(x)=x+3
x+ 3 = 0
x = -3

b) F(x)= -5x+20
-5x + 20 = 0
-5x = -20
x = 4

c) y= -3-3x
-3-3x = 0
-3x = 3
x = -1

d) y= 2x-6
2x - 6 = 0
2x = 6
x = 3
2014-04-20T00:05:47-03:00
 a) F(x) = x + 3
x + 3 = 0
x = 0 - 3
x = - 3
-------------------------------------------------------
b) F(x) = - 5x + 20
- 5x + 20 = 0
- 5x = 0 - 20
- 5x = - 20
x = - 20 : (- 5)
x = 4
-------------------------------------------------------
c) y = - 3 - 3x
- 3 - 3x = 0
- 3x = 0 + 3
- 3x = 3
x = 3 : (- 3)
x = - 1
-------------------------------------------------------
d) y = 2x - 6
2x - 6 = 0
2x = 0 + 6
2x = 6
x = 6 : 2
x = 3